The Impact of Hudud Law Implementation on Emotional Regulation and Psychological Stability in Society - Rahmadi, M. Agung; Al-Munawar, Said Agil Husin; Nasution, Helsa; Mawar, Luthfiah; Sihombing, Nurzahara; Lubis, Ismail Saleh (Islamic Law and Social Issues in Society, 2025)
This study investigates the psychological effects of ḥudūd law implementation, focusing on emotional regulation and psychological stability to address a significant gap in the legal psychology literature. While most discourse on ḥudūd law centers on its social and political dimensions, its influence on mental well-being remains underexplored. Using Structural Equation Modeling (SEM), data were collected from 827 respondents across four countries - Saudi Arabia, Iran, Malaysia, and Indonesia - that differ in their enforcement of ḥudūd law. Instruments such as the Emotion Regulation Questionnaire (ERQ) and Psychological Stability Scale (PSS) were employed. The findings reveal strong, statistically significant relationships between perceptions of ḥudūd law and emotional regulation (β = 0.67, p < 0.001) as well as psychological stability (β = 0.58, p < 0.001). The SEM model demonstrates an excellent fit (CFI = 0.94, RMSEA = 0.047, TLI = 0.92), with emotional regulation identified as a key mediating factor (indirect effect = 0.38, p < 0.001). Multi-group analysis shows significant variations based on cultural background (χ² = 18.76, df = 4, p < 0.01) and religiosity (χ² = 22.34, df = 4, p < 0.001), underlining the role of sociocultural context. The study also highlights the moderating influence of procedural justice perceptions (β = 0.42, p < 0.01), which shape how individuals psychologically experience ḥudūd law. These results not only reinforce earlier findings by Al-Rodiman (2013) and Razif (2020) but also provide a counterpoint to Efendi et al. (2025), who emphasized negative outcomes. Ultimately, this research contributes to a nuanced understanding of how religious legal systems affect community mental health and offers insights for developing psychologically informed approaches to ḥudūd law policy.